2021
DOI: 10.1017/s0033291721001380
|View full text |Cite
|
Sign up to set email alerts
|

Individual and environmental correlates of childhood maltreatment and exposure to community violence: Utilizing a latent profile and a multilevel meta-analytic approach

Abstract: Background Childhood maltreatment (CM) and exposure to community violence (ETV) are correlated with physical/mental health and psychosocial problems. Typically, CM and ETV are examined separately, by subtypes within category, or collapsed across both into one category of adversity. Consequently, research is limited in identifying subgroups of individuals with different amounts of exposure to both CM and ETV. Accordingly, we lack sufficient understanding of the extent to which problems associated with CM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
4
10
2
Order By: Relevance
“…For example, in terms of antisocial behavior, we found that only membership in one trajectory, Moderate PH/High ETV, predicted higher nonviolent crime three years later relative to the Low reference group. As hypothesized, our findings are consistent with previous studies documenting that moderate amounts of family stress in the context of high ETV is an especially potent combination for promoting nonviolent crime (Estrada et al, 2021). Nonviolent crime, which consists of behaviors including theft, selling drugs, and destroying property, can be motivated by a host of factors including one's ability to regulate behavior or a desire to gain resources (Gardner et al, 2008).…”
Section: Mental Health Outcomes Predicted By Joint Trajectory Membershipsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, in terms of antisocial behavior, we found that only membership in one trajectory, Moderate PH/High ETV, predicted higher nonviolent crime three years later relative to the Low reference group. As hypothesized, our findings are consistent with previous studies documenting that moderate amounts of family stress in the context of high ETV is an especially potent combination for promoting nonviolent crime (Estrada et al, 2021). Nonviolent crime, which consists of behaviors including theft, selling drugs, and destroying property, can be motivated by a host of factors including one's ability to regulate behavior or a desire to gain resources (Gardner et al, 2008).…”
Section: Mental Health Outcomes Predicted By Joint Trajectory Membershipsupporting
confidence: 91%
“…Further, the present study contributes to evidence suggesting that nuance in the relationships between combinations of stressful life experiences and mental health emerges when the relative amount of each stressful life experience is considered. Though some studies suggest that there is a dose-response relationship between the experience of multiple stressful life events and negative mental health outcomes (e.g., Chapman et al, 2004), results from the present study indicate that subgroups characterized by high levels of exposure to one stressful life event, in the context of moderate exposure to another, often show the strongest relationships to severe mental health outcomes (Estrada et al, 2021). Our results underscore the importance of understanding the subtype(s) and amount of exposure to multiple stressful life experiences when characterizing the relationships among life stressors and mental health outcomes.…”
Section: Mental Health Outcomes Predicted By Joint Trajectory Membershipcontrasting
confidence: 80%
See 1 more Smart Citation
“…CM has also been shown to increase lifetime psychopathology as evidenced by neural responses to threatening faces and LPP signaling (Sandre et al, 2018). Interestingly, CM is also more strongly associated with the development of later internalizing and externalizing symptoms, whereas ETV is more associated with externalizing symptoms only (Estrada et al, 2021, Aksoy et al, 2022. Currently, we know that children and adolescents typically show more symptoms of anxiety and anger, less verbalization of hopelessness, and less negative symptoms in comparison to adults' populations who have depression (Luyten & Fonagy, 2018).…”
Section: Key Differences In Youth and Adolescent Psychopathologymentioning
confidence: 99%
“…Although relatively less is known about the impact of specific types of adversity on neurobiological outcomes, extensive prior research has compared behavioral and clinical outcomes associated with different types of adversity (e.g., sexual abuse vs. physical abuse) to test whether specific exposures may be associated with differential outcomes (e.g., Cicchetti & Toth, 1995; Estrada et al., 2021; Gomez et al., 2017; Khan et al., 2015; McCoy, 2013). Relatedly, as previously described, an emerging line of research suggests that exposures characterized by threat versus deprivation may have differential effects on neurobiological (e.g., Colich et al., 2020) and clinical outcomes (e.g., Miller et al., 2018).…”
Section: Introductionmentioning
confidence: 99%